(untitled) (Journal of Economic Research & Business Administration, 2015)
This article focuses on the development of the agriculture sector and its share of contribution to the competitiveness of the economy of Kazakhstan. The authors found that the key factors for the contribution of agriculture to the competitiveness index are - “The effectiveness of the labor market” and “market size”, where the most significant place is given to the export potential of grain production. Important attention is paid to the aspects of the change in the share of agriculture in GDP and employment over the past 24 years in Kazakhstan. While there is an inverse relationship between employment and the contribution of this industry in the national income, which growth to 26% and decline to 5% respectively in 2013. The results revealed the problems of the agricultural sector, such as - deterioration of agricultural technology park, high interest rates on loans to farmers, poor storage and logistics for the delivery of grain, enough significant level of import dependence of the country on imports of foreign agricultural products and others, as well as recommendations on improving the performance of the agricultural sector and increase its contribution to the competitiveness of Kazakhstan.